Analisis Algoritma Apriori Dalam Menentukan Pola Pemesanan Konsumen Pada Ucokopi - Dewinta Marthadinata Sinaga; Wiranto Hernandesz Sirait; Agus Perdana Windarto (Journal of Informatics Management and Information Technology, 2021)
Ucokopi is a business engaged in the sale of food and beverages for the general public. The menus are served in the form of snacks such as french fries, fried rice, sausages and so on, as well as various drinks processed at economical prices, especially for students and students. The large number of consumer orders everyday will increase the amount of transaction data. Existing data can be processed to determine the combination of food and beverage menu itemset that consumers often buy so as to produce important information. The problem that often occurs is the unavailability of consumer order menus which are classified as in demand. This research was conducted in Pematangsiantar city. The purpose of this study was to analyze a sales strategy through the association search process. Based on these results, it can be obtained that if you buy Ginger Milk, it is 100% most likely to buy Sausages, if you buy Milk Coffee, 88% are most likely to buy Penyet Chicken Rice, if you buy Sausages then 75% are most likely to buy Potatoes. It is hoped that the research results can provide information to Ucok Cafe business owners in providing food and beverage stocks that are most in demand and can adjust the menu placement based on a combination of menu itemset that is formed to increase sales.